MIND MAPPING AS A MEDIA TO ENHANCE THE STUDENTS’ SCIENCE LEARNING OUTCOMES AT GRADE V SD ISLAM PERTIWI NUSANTARA MAKASSAR - Sumarnianti Usman; Arsad Bahri, Evi Ristiana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the influence of mind mapping on students’ learning outcomes. This study was conducted at SD Islam Pertiwi Nusantara, Makassar. The approach of this study was quantitative with a quasi-experimental design. The sampling technique used was simple random sampling. Data were collected through tests, questionnaires, and observations. The data were then analyzed using one-way covariate analysis (ANCOVA), after fulfilling the prerequisite tests, such as normality and homogeneity. The results of this study indicated that mind mapping had an influence on students’ learning outcomes, as shown by the ANCOVA significance value of 0.045, which means Sig. < 0.05.